ANALISA KUALITAS BRIKET ARANG (STUDI KASUS TANAMAN BAMBU DI HUTAN PENDIDIKAN DESA HONITETU KABUPATEN SERAM BAGIAN BARAT) - Jimmy Titarsole; Rohny S Maail (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
This study aims to analyze the relationship between bamboo (Javanese bamboo species (Schizostachyum brachycladum), petung bamboo (Dendrocalamus asper) and suanggi bamboo (Schizostachyum arundinaceae)] with pressure (3 tons, 2.5 tons and 2 tons treatment) on the quality of charcoal briquettes. The research procedure begins with the preparation of raw materials, drying, curing, grinding, adhesion, printing and pressing, drying briquettes and determining the quality of the briquettes. This study used a Completely Randomized Design (CRD) arranged in factorial with 3 replications where the factors studied were 2 factors: factor A (bamboo type) and factor B (pressure). The results showed that the analysis of bamboo species diversity (A) affected the air-dry water content and the heating value, pressure factor (B) and interaction (AB) affected the roughness of air-dried water while the other parameters did not affect. The value of dry air content ranges between 6.55-6.62%, Dry oven water levels range between 3.426-3.446%, ash content ranges between 4.154-4.240%, volatile substance levels range between 7.64-7.99%, bonded carbon content ranges between 60.295-60.456% and and heating value ranges from 4336.28-4833.24 cal/g. Research Results Meet SNI Standards SNI 01-6235-2000.